EFL STUDENTS’ RESPONSES TOWARDS THE USE OF ENGLISH TREND SONGS IN LISTENING CLASSROOM - Farah Nurfadilla; Kusrin Kusrin (PROJECT (Professional Journal of English Education), 2022)
This study entitled "EFL Students’ responses towards the use of English Trend songs in listening lesson". This study aims to determine student responses in learning listening through songs. This research is motivated by the phenomenon of listening to trending English songs among teenagers which has a big impact on learning English, especially in listening lessons. This study was conducted to see if listening to English songs could help them in listening lessons. In this study, researchers used qualitative research to find data with a case study model. 16 participants of this research are in the same university with different majors. Data were collected through a questionnaire. The results show that the use of songs in the listening class gets a positive response. They felt it introduced a unique learning environment, one that was more relaxed and pleasurable. Students were additionally motivated by English songs during the teaching and learning process. Keywords:  Case Study, EFL Student, English Trend Songs, Listening Classroom